EFEKTIVITAS MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA - Anna Rosmita (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
This study aims to know whether there is a significant influence of using PBL learning model on students’ mathematical problem solving ability at the eighth grade students of SMP Negeri 5 Siabu. The research was conducted by applying experimental method (one group pretest post test design) with 29 students as the sample and they were taken by using simple cluster sampling technique from 89 students. Observation and test were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using PBL model was 3.375 (good category) and (b) the average of students’ mathematical problem solving ability before using PBL was 50.51 (fair category) and after using PBL was 60.23 (enough category). Furthermore, based on inferential statistic by using pair sample ttest (SPSS 22), the result showed significant value was less than 0.05(0.000<0.05. It means, there is a significant influence of using PBL learning model on students’ mathematical problem solving ability at the eighth grade students of SMP Negeri 5 Siabu.